Using evolutionary data to make sense of macromolecules with a "face‐lifted" ConSurf. (21st February 2023) - Yariv, Barak; Yariv, Elon; Kessel, Amit; Masrati, Gal; Chorin, Adi Ben; Martz, Eric; Mayrose, Itay; Pupko, Tal; Ben‐Tal, Nir
Abstract: The ConSurf web‐sever for the analysis of proteins, RNA, and DNA provides a quick and accurate estimate of the per‐site evolutionary rate among homologues. The analysis reveals functionally important regions, such as catalytic and ligand‐binding sites, which often evolve slowly. Since the last report in 2016, ConSurf has been improved in multiple ways. It now has a user‐friendly interface that makes it easier to perform the analysis and to visualize the results. Evolutionary rates are calculated based on a set of homologous sequences, collected using hidden Markov model‐based search tools, recently embedded in the pipeline. Using these, and following the removal of redundancy, ConSurf assembles a representative set of effective homologues for protein and nucleic acid queries to enable informative analysis of the evolutionary patterns. The analysis is particularly insightful when the evolutionary rates are mapped on the macromolecule structure. In this respect, the availability of AlphaFold model structures of essentially all UniProt proteins makes ConSurf particularly relevant to the research community. The UniProt ID of a query protein with an available AlphaFold model can now be used to start a calculation. Another important improvement is the Python re‐implementation of the entire computational pipeline, making it easier to maintain. This Python pipeline is now available for download as a standalone version. We demonstrate some of ConSurf's key capabilities by the analysis of caveolin‐1, the main protein of membrane invaginations called caveolae.